Volatiles and food security : role of volatiles in agro-ecosystems - Choudhary, Devendra K.; Sharma, Anil K. (Molecular biologist); Agarwal, Prachi; Varma, A. 1939-; Tuteja, Narendra (Springer, 2017)
This book presents research on volatiles produced by microbes and plants along with their biotechnological implications for sustainable agriculture. A greater understanding of how plants and microbes live together and benefit each other can provide new strategies to improve plant productivity, while at the same time helping to protect the environment and maintain global biodiversity. To date, the use of chemicals to enhance plant growth or induced resistance in plants has been limited due to the negative effects and the difficulty in determining the optimal concentrations to benefit the plant. The book discusses extensive studies on biological alternatives that avoid these problems, and the research presented suggests that these compounds could offer an environmentally sound means to better grow and protect plants under greenhouse or field conditions. To understand the nature of VOCs and gene expression profiling of plant genes responding against these compounds can be conducted. It is possible that VOCs produced by microbes while colonizing roots are generated at sufficient concentrations to trigger plant responses. In conclusion, positive or negative effects of VOCs on plant productivity will be dependent on upon specific VOCs microbial strain, plant genotype, and presence/absence of abiotic/biotic stresses.
Keywords: Plant-microbe relationships.; Bacteriology, Agricultural.; Volatile organic compounds.; elektronické knihy; electronic books